Length-weight Relationship and Reproduction of Halfbeak Hemiramphus lutkei Valenciennes, 1847 In The Waters Around Nain Island, North Minahasa Regency - Umasangadji, Muhammad Hasril; Bataragoa, Nego E.; Kondoy, Khristin I. F.; Lumingas, Lawrens .J. L .; Mantiri, Rose. O.S.E; Lumoindong, Frans (Jurnal Ilmiah Platax, 2023)
Abstract The waters around Nain Island have quite a lot of biological resources. One of the resources in these waters is the halfbeak Hemiramphus lutkei. This study aims to determine the relationship between length-weight and reproduction of the halfbeak Hemiramphus lutkei. The length-weight relationship, growth patterns and condition factors. Reproduction includes sex ratio, gonadal maturity level, gonadal maturity index and fecundity. Fish sampling were taken from the catches of fishermen. The number of samples required is 200, the samples are taken twice in two months from June-July. The length-weight relationship of male was W= 0.1705L1.8204 negative allometric growth pattern and female fish W = 0.0572L2.1962 negative allometric growth pattern. The condition factor of male and female where 0.98 ± 0.06 and 1.03 ± 0.07 respectively. The sex ratio of male and female (1: 0.835). The gonad maturity level of male (immature, developing, mature, ripe and spent) was found in June and female (immature, developing, mature, ripe and spent) found in June and July. The fecundity of ranged from 923 – 3,578 eggs with an average of 1,899 ± 666. Keywords: Length-weight, growth patterns, gonad, fekundity ABSTRAK Perairan Sekitar Pulau Nain ialah perairan yang memiliki cukup banyak sumberdaya hayatinya. Salah satu sumberdaya yang berada di perairan tersebut yaitu, ikan julungjulung Hemiramphus lutkei. Penelitian ini bertujuan untuk mengetahui hubungan panjang-berat dan reproduksi ikan julungjulung Hemiramphus lutkei. Hubungan panjang-berat meliputi pola pertumbuhan dan faktor kondisi. Reproduksi meliputi rasio kelamin, tingkat kematangan gonad, indeks kematangan gonad dan fekunditas. Lokasi pengambilan sampel ikan diambil di perairan sekitar Pulau Nain dan sampel diambil dari hasil tangkapan nelayan. Jumlah sampel yang diperlukan sebanyak 200 ekor, sampel diambil sebanyak dua kali dalam dua bulan dari Juni-Juli. Hubungan panjang-berat ikan julungjulung jantan yaitu W= 0,1705L1,8204 pola pertumbuhan allometrik negatif. Ikan julungjulung betina W = 0,0572L2,1962 pola pertumbuhan allometrik negatif. Faktor kondisi ikan julungjulung jantan dan betina bernilai 0,98 ± 0,06 dan 1,03 ± 0,07. Rasio kelamin ikan julungjulung jantan dan betina (1:0,835). Tingkat kematangan gonad ikan julungjulung jantan (I, II, III, IV dan V) ditemukan pada setiap bulan Juni. Tingkat kematangan gonad ikan julungjulung betina (I, II, III, IV dan V) ditemukan pada setiap sampel pada bulan Juni maupun Juli. Fekunditas ikan julungjulung berkisar antara 923 – 3.578 butir dengan rata-rata 1.899 ± 666. Kata Kunci: Panjang-berat, pola pertumbuhan, gonad, fekunditas